2-D HORIZONTAL COUPLED HYDRODYNAMIC-TRAJECTORY MODEL OF FLOATING MARINE DEBRIS IN AMBON BAY - HUGO SAMUDRA PUTUHENA (NIM : 12909011); Pembimbing : Ivonne M. Radjawane, Ph. D
Problem of floating marine debris (FMD), affecting the environmental degradation that negatively impact other aspects in the waters of Ambon Bay. Therefore, to study the problems of the FMD, a coupled hydrodynamic and FMD trajectory model was conducted to determine the pattern of FMD movement in the bay. The model area including the topography condition of the bay, which has a sill separating the Inner and the Outer Ambon Bay. Hydrodynamic simulations using tidal and wind as the driving force. FMD trajectory model simulated with two different scenarios. In the first scenario, FMD sourced from sea, with a point source located at the ferry traffic lane between Poka and Galala waters at the border between the sill and the Inner Ambon Bay. The simulation model runs run for 18 days on 07/04/12-25/04/12. In scenario 2, FMD sourced from land, located along the coast of Mardika Market (Inner Ambon Bay). Simulated for 4 months on 07/04/12-04/07/12. SLT trajectory simulation results, showing the percentage distribution of the first scenario SLT for 18 days in April 2012. Amounted to 88.8% of SLT piled in Ambon Bay area. Meanwhile, the percentage distribution of the results of the second scenario SLT for 4 months in April-July 2012, showing 90% SLT stacked in Ambon Bay area Affairs, 10% were in the sill.